IMPROVEMENT OF TYPES OF INFORMATIONAL RISK INSURANCE - Xolbayev Azamat Yuldashovich (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation. In this scientific work, the role of insurance mechanisms in eliminating the types of informational risks and the losses arising from them is analyzed in conditions where modern digital technologies and information systems are rapidly developing. The main focus is on covering the risks of types of informational risk insurance — cybersecurity, data security insurance and information infrastructure. The work studied the development trends of informational risk insurance systems based on the experience of foreign countries, and developed practical proposals and recommendations for improving insurance services of this type in the conditions of Uzbekistan. Proposals have also been made for informational risk assessment methodologies for insurance companies, the formation of a tariff system and the strengthening of the legal framework. The results of the study are important in diversifying the insurance market, expanding the possibilities of financially compensating for possible losses in the field of cybersecurity, as well as supporting the digital economy.